2013
DOI: 10.1111/hiv.12068
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes and regional differences in treatment uptake of hepatitis C therapy in EuroSIDA

Abstract: ObjectivesAll HIV/hepatitis C virus (HCV)-coinfected patients with chronic HCV infection and ≥ F2 fibrosis should be considered for HCV therapy. This study aimed to determine the rate of HCV treatment uptake among coinfected patients in Europe.MethodsEuroSIDA patients with viraemic HCV infection were included in the study. Poisson regression was used to identify temporal changes and regional differences in HCV treatment uptake.ResultsA total of 1984 patients were included in the study, with a median follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Large European cohorts report between 25% and 30% of co-infected patients initiate HCV therapy. 8,9 The majority of US studies report 15% or less. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Large European cohorts report between 25% and 30% of co-infected patients initiate HCV therapy. 8,9 The majority of US studies report 15% or less. 10 …”
Section: Introductionmentioning
confidence: 99%
“…The study by Ioannou et al [21] reported that only 994 out of 5999 (18%) HIV-HCV-co-infected patients assisted by the Veterans Affairs healthcare system received an interferon-based regimen. This percentage rises to 25.3% in the EuroSIDA cohort but is accompanied by a reduction in treatment incidence in 2009 [22]. The proper timing at which to begin pegylated interferon and ribavirin treatment, associated with DAA when indicated, must take HIV disease status into account, but such coordination is not an easy task.…”
Section: Discussionmentioning
confidence: 99%
“…Patients residing in southern Europe have been more likely to receive HCV treatment compared with patients from other EuroSIDA regions. The decrease in recent years is probably explained by treatment saturation of the patients in urgent need of therapy, as well as by patients and physicians waiting for better treatment options [2,7]. Among the proportion of co-infected patients with information on fibrosis available, only one-third of treated patients had significant fibrosis (METAVIR F2 or greater), while 22% of untreated patients had significant fibrosis.…”
Section: Uptake Of Hcv Treatment In Eurosida: Are the Right Patients mentioning
confidence: 99%
“…Among the proportion of co-infected patients with information on fibrosis available, only one-third of treated patients had significant fibrosis (METAVIR F2 or greater), while 22% of untreated patients had significant fibrosis. Hence many patients with minimal short- to intermediate-term risk of HCV-related complications received a costly treatment associated with many adverse effects, while many patients at risk of complications of their HCV infection did not receive relevant treatment [2]. …”
Section: Uptake Of Hcv Treatment In Eurosida: Are the Right Patients mentioning
confidence: 99%